Marginal Strength of Collarless Metal Ceramic Crown - Sikka Swati; R. Chowdhary; P. S. Patil (Hindawi Limited, 2010)
Metal ceramic restorations have been implicated for the discoloration in area of labiogingivalmargin. Attempts to rectify this, by altering the design of metal frameworkswill lead to decrease in fracture strength atmargin. This in vitro study compared the fracture strength at margins of metal ceramic crowns cemented to metal tooth analogs. Crowns evaluated with different marginal configurations, shoulder and shoulder bevel with 0 mm, 0.5 mm, 1 mm, and 1.5 mm, were selected. Methods. Maxillary right canine typhodont tooth was prepared to receive a metal ceramic crown with shoulder margin. This was duplicated to get 20 metal teeth analogs. Then the same tooth was reprepared to get shoulder bevel configuration. These crowns were then cemented onmetal teeth analogs and tested for fracture strength atmargin on an Instron testing machine. A progressive compressive load was applied using 6.3 mm diameter rod with crosshead speed of 2.5 mm per minute. Statisticaly analysis was performed with ANOVA, Student's "t" test and "f" test. Results. The fracture strength of collarless metal ceramic crowns under study exceeded the normal biting force. Therefore it can be suggested that collarless metal ceramic crowns with shoulder or shoulder bevel margins up to 1.5 mm framework reduction may be indicated for anteriormetal ceramic restorations. Significance. k Collarless metal ceramic crowns have proved to be successful for anterior fixed restorations. Hence, it may be subjected to more clinical trials.